The Construction of Gender Subordination in Arabic Language Textbooks: A Roland Barthes Semiotic Study - Muhammad Alghiffary; Abdul Mukhlis; Chilya Aghnis Shalica (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This study examines the phenomenon of gender bias embedded within the technical structure of Arabic textbooks, a pedagogical tool often perceived as a neutral medium for knowledge transfer. Specifically, it aims to uncover gender subordination within Muhammad Yusron’s Qawāid al-Lughah al-Arabiyyah through the lens of Roland Barthes’ semiotics. Employing a qualitative-descriptive method, the analysis scrutinizes three primary instructional components: reading materials (al-qirā’atu), grammatical rules (al-qawāidu), and exercises (al-tadrībātu), to deconstruct the two-stage signification system of denotation and connotation. The findings reveal that gender subordination is systematically manifested through the dominance of male subjects as the primary centers of intellectual, social, and religious authority. Semiotically, the marginalization of female representation and the use of collective diction, such as substituting zaujah (wife) with usrah (family), serve as potent indicators of